2009
DOI: 10.3109/02713680903125329
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Curcumin on Lung Resistance-Related Protein (LRP) in Retinoblastoma Cells

Abstract: These results demonstrate that curcumin modulated the expression of LRP in the Y79 retinoblastoma cell line. Thus, curcumin may be used as a chemosensitizer to make the retinoblastoma cells more sensitive to the effects of chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 20 publications
(23 reference statements)
0
15
0
Order By: Relevance
“…In our earlier study, we have performed MTT assay to determine the relative cytotoxicity of curcumin in the Y79 RB cell line (data not shown; [30]). The concentrations that were less toxic to cells were chosen for further experiments.…”
Section: Discussionmentioning
confidence: 99%
“…In our earlier study, we have performed MTT assay to determine the relative cytotoxicity of curcumin in the Y79 RB cell line (data not shown; [30]). The concentrations that were less toxic to cells were chosen for further experiments.…”
Section: Discussionmentioning
confidence: 99%
“…[184] Another study has suggested that curcumin blocks proteins involved with multidrug resistance in the Y79 cell line. [185] Co-administration of curcumin with other chemotherapy agents may, like cyclosporine, act as a chemosensitizer to improve retinoblastoma cell sensitivity to chemotherapy. [185] However, the use of antioxidants must be very cautiously considered in combination therapies for retinoblastoma, as generation of reactive oxygen species (ROS) to increase cellular oxidative-stress has been implicated as an important mechanism of action for many of the novel agents recently investigated.…”
Section: In Vitro Testingmentioning
confidence: 99%
“…The protein is encoded by LRP gene and mechanism of action of this protein in eliciting MDR is yet to be explored. It has been investigated intensively that, these two proteins (MRP-1 and LRP) are solely associated with multidrug resistance in retinoblastoma [6], [7]. Thus, considering the relative importance of MDR in retinoblastoma, there is an urgent call for effective therapeutic strategy in retinoblastoma therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Thiyagarajan et al . have explored that; curcumin can down regulate the expression of LRP protein and mRNA in a concentration dependent manner in Y79 retinoblastoma cell line [7]. Additionally, curcumin has potent anticancer properties as demonstrated in a plethora of human cancer cell line and animal carcinogenesis model [14].…”
Section: Introductionmentioning
confidence: 99%